1999
DOI: 10.1556/004.47.1999.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Oxytocin Antagonist on Prostaglandin F2α Secretion and the Course of Luteolysis in Sows

Abstract: The role of oxytocin (OT) in the regulation of prostaglandin F2 alpha (PGF2 alpha) secretion during luteolysis in gilts was studied using a highly specific OT antagonist (CAP-581). In Experiment 1 gilts on Days 14 to 19 of the oestrous cycle in Latin square design were used, to determine the dose and time of application of OT and CAP. In Group I (n = 6) gilts were treated intravenously with saline or with 10, 20 and 30 IU of OT. Concentrations of the main PGF2 alpha metabolite i.e. 13,14-dihydro-15-keto-prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
(43 reference statements)
1
19
1
1
Order By: Relevance
“…In ewes, luteal OXT acts through endometrial OXT receptors to generate a PGF 2a pulse which in turn stimulates further secretion of OXT as well as inducing functional regression of the CL through inhibiting progesterone synthesis (reviewed in Jenkin (1992)). In the pig, OXT may not be responsible for the initiation of luteolysis but is more likely involved in the control of pulsatile release of PGF 2a , especially the height and frequency of the peaks of this hormone during luteolysis (Kotwica et al 1999). Surprisingly, OXT concentration in the uterine lumen significantly increases on days 12-14 of pregnancy compared with the corresponding days of the estrous cycle (Vallet et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In ewes, luteal OXT acts through endometrial OXT receptors to generate a PGF 2a pulse which in turn stimulates further secretion of OXT as well as inducing functional regression of the CL through inhibiting progesterone synthesis (reviewed in Jenkin (1992)). In the pig, OXT may not be responsible for the initiation of luteolysis but is more likely involved in the control of pulsatile release of PGF 2a , especially the height and frequency of the peaks of this hormone during luteolysis (Kotwica et al 1999). Surprisingly, OXT concentration in the uterine lumen significantly increases on days 12-14 of pregnancy compared with the corresponding days of the estrous cycle (Vallet et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic infusions of OXT antagonist between days 12 and 20 of the estrous cycle reduce the amplitude of PGF 2a metabolite (PGFM) pulses, but do not prevent luteolysis (Kotwica et al 1999). In pigs, the neurohypophysis provides a greater amount of circulating OXT than does the CL during the luteal phase, and plasma OXT increases during luteolysis (Kotwica et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In pigs it is suggested that OT can be involved in the secretion of luteolytic PGF2a peaks but its role is limited only to controlling their height and frequency, since PGF 2 (, release and luteolysis in sows was not prevented by blocking the OT receptors [23].…”
mentioning
confidence: 99%